2023
DOI: 10.1186/s44280-023-00009-9
|View full text |Cite
|
Sign up to set email alerts
|

Current status and trends of antimicrobial resistance among clinical isolates in China: a retrospective study of CHINET from 2018 to 2022

Abstract: Antimicrobial resistance (AMR) is a pressing issue in China, with antibiotic therapy becoming less effective against bacterial infections. To address this challenge, the China Antimicrobial Surveillance Network (CHINET) was established in 2005 to monitor antimicrobial resistance in the country. This study analyzed the CHINET data from teaching hospitals and evaluated the trends of AMR in China from 2018 to 2022. A range of 163,636 to 301,917 isolates was obtained per year, with the majority being Gram-negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…21 The monitoring data by the China Antimicrobial Surveillance Network (CHINET) showed that the resistance rate of CRAB to colistin sulfate was very low (around 1.0%). 22 Unfortunately, studies revealed that only 5% of intravenous colistin crossed into the CSF, and this penetration ratio did not exceed 25% even in patients with meningitis whose blood-brain barrier was disrupted. 23 IVT is a method of injecting a drug directly into the subarachnoid space through a lumbar puncture, allowing the drug to infiltrate the CSF without passing through the blood-brain barrier and reaching its effective concentration quickly.…”
Section: Discussionmentioning
confidence: 99%
“…21 The monitoring data by the China Antimicrobial Surveillance Network (CHINET) showed that the resistance rate of CRAB to colistin sulfate was very low (around 1.0%). 22 Unfortunately, studies revealed that only 5% of intravenous colistin crossed into the CSF, and this penetration ratio did not exceed 25% even in patients with meningitis whose blood-brain barrier was disrupted. 23 IVT is a method of injecting a drug directly into the subarachnoid space through a lumbar puncture, allowing the drug to infiltrate the CSF without passing through the blood-brain barrier and reaching its effective concentration quickly.…”
Section: Discussionmentioning
confidence: 99%
“…The methods were consistent in all participating hospitals, which were verified every year. 6 The CARSS protocol of AST was the same with CHINET.…”
Section: Amr Surveillance System In Chinamentioning
confidence: 99%
“… 8 , 9 The resistance rates of colistin and tigecycline in E. coli have fluctuated around 1.0% and 0.1%, respectively, over the recent 5 years. 6 …”
Section: Amr Prevalence and Trends In Gram-negative Bacillimentioning
confidence: 99%
See 1 more Smart Citation
“…The established national phenotypic antimicrobial resistance surveillance program—the Japan Nosocomial Infections Surveillance (JANIS) ( 19 , 20 )—reported that the carbapenem (meropenem) resistance rate of P. aeruginosa in hospitalized patients in Japan, as of 2020, was 10.5%. This was the average among representative countries where antimicrobial resistance surveillance for P. aeruginosa was once or is currently being performed; the resistance rate was 29.3% in India (ATLAS 2015–2019), 19.3% in China (CHINET 2020), 6.5% in Australia (ATLAS 2015–2019), 28.5% in Poland (EARS-net 2020), 15.7% in the Czech Republic (EARS-net 2020), 13.9% in Germany (EARS-net 2020), 12.6% in France (EARS-net 2020), and 3.7% in Finland (EARS-net 2020) ( 16 , 21 , 22 ).…”
Section: Introductionmentioning
confidence: 99%